1977
DOI: 10.1111/j.1471-0528.1977.tb12492.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hormone Replacement Therapy on Glucose Tolerance in Postmenopausal Women

Abstract: Oral glucose tolerance tests were performed on 50 symptomatic postmenopausal women before and after three months of hormone replacement therapy. All patients were randomly allocated to one of five groups treated with various synthetic or so-called naturally occurring oestrogens. Therapyproduced a significant deterioration of carbohydrate tolerance with sequential preparations containing 100 pg of ethinyl oestradiol or graduated doses of mestranol up to 50 pg. The conjugated equine oestrogen (1.25 mg daily) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

1981
1981
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(8 citation statements)
references
References 15 publications
2
6
0
Order By: Relevance
“…The results of serum glucose estimations suggested no differences in carbohydrate metabolism between the two groups, although there was a significant reduction in the glucose level in the postmenopausal group following treatment. Previous studies have shown mild impairment of glucose tolerance associated with the same hormone treatment as that used in the present study (Sturdee et al, 1976;Thom et al, 1977).…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…The results of serum glucose estimations suggested no differences in carbohydrate metabolism between the two groups, although there was a significant reduction in the glucose level in the postmenopausal group following treatment. Previous studies have shown mild impairment of glucose tolerance associated with the same hormone treatment as that used in the present study (Sturdee et al, 1976;Thom et al, 1977).…”
Section: Discussionsupporting
confidence: 59%
“…Previous studies have shown mild impairment of glucose tolerance associated with the same hormone treatment as that used in the present study (Sturdee et al, 1976;Thom et al, 1977). Previous studies have shown mild impairment of glucose tolerance associated with the same hormone treatment as that used in the present study (Sturdee et al, 1976;Thom et al, 1977).…”
Section: Discussionsupporting
confidence: 54%
“…Enhanced insulin sensitivity, measured by the disappearance of glucose in an insulin tolerance test, has also been shown with 0·625 mg of oral CEE (Krauss et al ., 1988; Wilcox et al ., 1997), while a larger dose of CEE (1·25 mg) decreased insulin sensitivity. The effects of oral oestradiol on glucose and insulin metabolism also seem to be moderate (Larsson‐Cohn & Wallentin, 1977; Thom et al ., 1977; Silfverstolpe et al ., 1980), which is in agreement with our results.…”
Section: Discussionmentioning
confidence: 99%
“…An impaired glucose tolerance and increased serum levels of insulin have been observed following treatment with both synthetic and "natural" estrogens. So far, no causal relationship between estrogen substitution and diabetes has been established (49,58,80,86,97). Certain metabolic effects of estrogens are at present regarded as beneficial.…”
Section: Estrogens and Hepatic Protein Synthesis (11 111)mentioning
confidence: 99%